Blood will out : the true story of a murder, a mystery, and a masquerade - Kirn, Walter, 1962- (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2014)
The true story of a young novelist who meets and befriends an eccentric, privileged New Yorker when he delivers a crippled hunting dog to him from an animal shelter, and later discovers that his friend was a serial imposter and brutal double-murderer.